Arremessadas da turma de caminhão: literatura e experiência traumática entre as trabalhadoras boias-frias na obra de Murilo Carvalho - Medina, Ettore Dias; Souza, Eliana Maria de Melo [UNESP] (My University, 2012)
This article investigates the universe of women seasonal farm workers, more precisely those women laborers who take the so-called truck, in the newspaper chronicle “Th e Seasonal Farm Workers’ Express” (1976) and the short story “Th e funny face of fear”(1978), both by the journalist and creative writer Murilo Carvalho. Th e hypothesis is that these two narratives, in which the theme is the truck accident, can be classifi ed as testimonial literature.

Este artigo investiga o universo das trabalhadoras boias-frias, mais precisamente as que pegam o chamado caminhão de turma. Assim, a reportagem “O Expresso Boia-Fria” (1976) e o conto “A cara engraçada do medo” (1978), ambos do jornalista e escritor brasileiro Murilo Carvalho, compõe o material investigado. Tem-se por hipótese que as duas narrativas, cujo tema é o acidente no caminhão de turma, se enquadram no universo da literatura de testemunho.
Keywords: Brazilian literature; Testimonial literature; Murilo Carvalho; Women seasonal farm workers; Outfi t truck accident; Literatura brasileira; Literatura de testemunho; Murilo Carvalho; Trabalhadoras boias-frias; Acidente no caminhão de turma